MODELING OF TECHNICAL AND TACTICAL TRAINING OF JUDOKAS OF 19-21 YEARS OLD OF MIDDLE WEIGHT CATEGORIES ON THE BASIS OF ANALYSIS OF COMPETITIVE ACTIVITY (Physical Culture and Sport: Scientific Perspective, 2023)
The article investigates the analysis of the competitive activity of judokas aged 19-21 years in middleweight categories with the aim of developing models of technical and tactical training. The article analyzes 60 competitive fights of judokas of 19-21 years old of weight categories up to 60 kg and up to 66 kg. The indicators of judokas of the control (30 fights) and experimental (30 fights) groups at the Ukrainian Junior Championship (U21), 2022, the Ukrainian Senior Championship, 2022 were analyzed. The following indicators were recorded: the number of real attempts to perform a technical action; the number of effective technical actions: judged by the judges as half a victory; the number of effective technical actions: judged by the judges as a clean victory; percentage of technical actions in the total number of technical actions; effectiveness of attacking actions (%); number of comments; number of disqualifications; number and percentage of rounds that ended within the allotted time; number and percentage of rounds that ended early; number and percentage of rounds that ended in extra time; number of combinations of technical actions; number of counterattacks. This suggests that the bouts are quite dynamic and require activation of the athlete from the first minutes of the fight. The nature of the remarks can be explained by the use of waiting tactics for the realization of counterattacks. It was found that during fights athletes use more counterattacks than combination techniques associated with offensive tactics. It was also found that the fight in judo mainly takes place in the stance. It was found that in fights, the throw from the knees is used the most times out of all technical actions. Such throws as behind the back, front kneeling kick, hook from the inside under the same leg, and deflection are not effective at all. Also throws that are quite effective with a small number of applications in a fight were found: a throw with a shin rest in the thigh, a catch and a throw with a turn with the hands. Moreover, the analysis of competitive activity allowed to establish that when performing a throw with the emphasis of the lower leg in the thigh judokas often get on the hold. On the basis of the analysis of competitive activity of judokas of 19-21 years old of middle weight categories the models of technical and tactical preparation of offensive and counterattacking tactics were developed. Both models included: improvement of throws, which are characterized by high efficiency during competitions (throw with a shin rest in a thigh, catch and throw with a turn with hands), improvement of a throw, which is used the most times in a fight but has rather low efficiency (throw through a back from knees). The difference between the models was that the model of offensive tactics additionally included the improvement of combination technique, improvement of endurance, and the model of counterattacking tactics - improvement of counterattacking technique, improvement of coordination abilities.
Keywords: judo; technical and tactical skills; coordination abilities; tasks; exercises